BS ISO/IEC 29110-4-2. Systems and software engineering. Lifecycle profiles for Very Small Entities (VSEs). Part 4-2. Software engineering. Profile specifications: Organizational management profile group (13th September 2019) - British Standards Institution,
No abstract available